Elements of digital transformation in dynamic capabilities in a Brazilian capital - Mendonça, Cláudio Márcio Campos de (2018)
The objective of the article was to describe the use and importance of elements of digital transformation (IoT, Big Data and Artificial Intelligence) as support for processes of dynamic capabilities in organizations of a Brazilian capital. A research is characterized as exploratory and descriptive, with a quantitative approach. 53 questionnaires were selected from business managers and IT managers. It has been identified that in the perception of business and IT managers the elements of digital transformation, even with relatively low information, mainly from IoT and IA, with a better focus on Big Data, are evaluated with importance, both nowadays, as well as in practice, up to 2025, in processes involving the dynamic capabilities of analyzing the environment (Sensing), seizing opportunities and managing as threats and transformations (Managing Threats / Transforming). With greater emphasis on Big Data in the processes of the dynamic ability to seize as opportunities.